What Is the 10-year Survivorship of Cemented Distal Femoral Endoprostheses for Tumor Reconstructions and What Radiographic Features Are Associated with Survival?. Issue 11 (November 2020) - Piakong, Pongsiri; Kiatisevi, Piya; Yau, Raymond; Trovarelli, Giulia; Lam, Ying-Lee; Joyce, David; Ruggieri, Pietro; Temple, H. Thomas; Letson, Douglas; Binitie, Odion
Abstract: Background: Aseptic loosening is one of the most common causes of revision of distal femoral endoprostheses and is considered a mid- to long-term complication. There are not many reports of 10-year survivorship free from aseptic loosening and all-cause survivorship in cemented stems. To our knowledge, there are no reports on radiographic features that are associated with aseptic loosening of these implants. Questions/purposes: (1) What is the 5- and 10-year survivorship free from aseptic loosening in patients undergoing reconstruction with a cemented distal femoral endoprosthesis after a tumor resection? (2) What is the all-cause 5- and 10-year survivorship at in these patients? (3) What radiographic features are associated with aseptic loosening at long-term follow-up? Methods: We performed a multicenter retrospective study reviewing aseptic loosening in cemented prostheses to determine radiographic features associated with long-term implant survivorship. Patients who underwent a cemented distal femoral reconstruction with a modular endoprosthesis after resection of a musculoskeletal tumor between 1997 and 2017 were reviewed. A total of 246 patients were identified from five institutions and met initial inclusion criteria. Of those, 21% (51) were lost to follow-up before 2 years, leaving 195 patients available for us to evaluate and analyze the survivorship and radiologic features associated with long-term implant survival. The mean (range) follow-up was 78 months (22 to 257). At the time of this analysis, 69% (135 of 195) of the patients were alive. Osteosarcoma was the most common diagnosis in 43% of patients (83 of 195), followed by metastatic carcinoma 13% (25 of 195). Fifty-six percent (110 of 195) of patients received chemotherapy; 15% (30 of 195) had radiation therapy. Aseptic loosening was diagnosed radiographically and was defined as a circumferential radiolucent line on all views, or subsidence around the stem in the absence of infection. We present 5- and 10-year Kaplan-Meier survivorship free from aseptic loosening, 5- and 10-year all-cause survivorship, and a qualitative assessment of radiographic features potentially associated with aseptic loosening (including the junctional radiolucent area, and cortical expansion remodeling). The junctional radiolucent area was defined as a radiolucent area of the bone starting at the bone-endoprosthesis junction to the tip of the femoral stem, and cortical expansion remodeling was defined as an increased cortical thickness at the stem tip. Although we wished to statistically analyze radiographic factors potentially associated with aseptic loosening, we did not have enough clinical material to do so (only nine patients developed loosening). Instead, we will report a few preliminary qualitative observations, which necessarily are preliminary, and which will need to be confirmed or refuted by future studies. We urge caution in interpreting these findings because of the very small numbers involved. Results: Kaplan-Meier survivorship free from aseptic loosening of the femoral component at 5 and 10 years were 95% (95% CI 89 to 98) and 93% (95% CI 86 to 97), respectively. Kaplan-Meier survivorship free from revision for any cause at 5 and 10 years were 74% (95% CI 65 to 79) and 64% (95% CI 49 to 70), respectively. Although the numbers were too small to analyze statistically, all patients with aseptic loosening had a junctional radiolucent area more than 20% of the total length of the stem without cortical expansion remodeling at the stem tip. No aseptic loosening was observed if there was cortical expansion remodeling, a junctional radiolucent area less than 20%, or curved stems that were 13 mm or greater in diameter. The numbers of patients with aseptic loosening in this series were too small to analyze statistically. Conclusions: Cemented distal femoral endoprostheses have a relatively low rate of aseptic loosening and acceptable projected first-decade survivorship. The presence of a radiolucent area more than 20% without cortical expansion remodeling at the stem tip may lead to aseptic loosening in patients with these implants. Close radiographic surveillance and revision surgery may be considered for progressive lucencies and clinical symptoms of pain. If revision is contemplated, we recommend using larger diameter curved cemented stems. These are preliminary and provisional observations based on a low number of patients with aseptic loosening; future studies with greater numbers of patients are needed to validate or refute these findings. Level of Evidence: Level III, therapeutic study.